Comparing Safety and Efficacy of Rivaroxaban with Warfarin for Patients after Successful Stent Placement for Chronic Iliofemoral Occlusion: A Retrospective Single Institution Study. (March 2021) - Zhang, Xing; Huang, Jiaqi; Peng, Zhiyou; Lu, Xinwu; Yang, Xinrui; Ye, Kaichuang
Abstract : Objective: The aim was to compare the safety and effectiveness of rivaroxaban and warfarin as anticoagulants for treating patients with post-thrombotic syndrome (PTS) with chronic iliofemoral venous occlusion undergoing iliofemoral venous stenting. Methods: This single institution retrospective study analysed patients with PTS with chronic iliofemoral venous occlusion who were prescribed rivaroxaban or warfarin for one year after successfully undergoing iliofemoral venous stenting. The primary safety and efficacy endpoints were bleeding complication rate and primary patency rate at one year. Secondary outcomes included Villalta score, symptom recurrence rate, ulcer healing rate, and clinically driven target lesion revascularisation (CD-TLR) rate during follow up. Results: From January 2016 to December 2017, 154 legs from 154 patients were included in this study (69 in rivaroxaban group and 85 in warfarin group). The groups were well matched for patient demographics, clinical characteristics, and procedural details. There was no significant difference between the rivaroxaban group and warfarin group in bleeding complication rate (10% vs. 16%, p = .23, hazard ratio [HR] 0.58, 95% confidence interval [CI] 0.25 – 1.37) at one year, as well as major bleeding complication rate (0% vs. 2%, p = .20, HR 0.16, 95% CI 0.01 – 2.61) and minor bleeding complication rate (10% vs. 14%, p = .40, HR 0.67, 95% CI 0.27 – 1.66). The primary patency rate was higher in the rivaroxaban group at one year (84% vs. 71%, p = .049, HR 0.50, 95% CI 0.26 – 0.96) and at two years (79% vs. 63%, p = .037, HR 0.52, 95% CI 0.29 – 0.93). At a mean follow up of 24 months (range 1 – 42 months), the rivaroxaban group had a significantly lower post-operative Villalta score (4.87 ± 3.51 vs. 6.88 ± 5.85, p = .010, t = 2.64, 95% CI 0.50 – 3.52), lower rate of symptom recurrence (4% vs. 32%, p < .001), lower CD-TLR rates (3% vs. 13%, p = .039), and higher ulcer healing rate (90% vs. 59%, p = .004) than the warfarin group. Conclusion: For PTS patients with chronic iliofemoral venous occlusion undergoing iliofemoral venous stenting, rivaroxaban probably exhibited similar safety but superior efficacy to warfarin. However, further prospective control studies with large sample size are necessary to confirm the results.